Durable Polymer Versus Biodegradable Polymer Drug-Eluting Stents After Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome: The HOST-REDUCE-POLYTECH-ACS Trial. Issue 11 (18th November 2020) - Kim, Hyo-Soo; Kang, Jeehoon; Hwang, Doyeon; Han, Jung-Kyu; Yang, Han-Mo; Kang, Hyun-Jae; Koo, Bon-Kwon; Kim, Seok Yeon; Park, Keun-Ho; Rha, Seung-Woon; Shin, Won-Yong; Lim, Hong-Seok; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Large-scale randomized comparison of drug-eluting stents (DES) based on durable polymer versus biodegradable polymer technology is currently insufficient in patients with acute coronary syndrome (ACS). The present study aimed to prove the noninferiority of the durable polymer DES (DP-DES) compared with the biodegradable polymer DES (BP-DES) in such patients. Methods: The HOST-REDUCE-POLYTECH-ACS (Harmonizing Optimal Strategy for Treatment of Coronary Artery Diseases—Comparison of Reduction of Prasugrel Dose or Polymer Technology in ACS Patients) trial is an investigator-initiated, randomized, open-label, adjudicator-blinded, multicenter, noninferiority trial comparing the efficacy and safety of DP-DES and BP-DES in patients with ACS. The primary end point was a patient-oriented composite outcome (a composite of all-cause death, nonfatal myocardial infarction, and any repeat revascularization) at 12 months. The key secondary end point was device-oriented composite outcome (a composite of cardiac death, target-vessel myocardial infarction, or target lesion revascularization) at 12 months. Results: A total of 3413 patients were randomized to receive the DP-DES (1713 patients) and BP-DES (1700 patients). At 12 months, patient-oriented composite outcome occurred in 5.2% in the DP-DES group and 6.4% in the BP-DES group (absolute risk difference, –1.2%; P non inferiority <0.001). The key secondary end point, device-oriented composite outcome, occurred less frequently in the DP-DES group (DP-DES vs BP-DES, 2.6% vs 3.9%; hazard ratio, 0.67 [95% CI, 0.46–0.98]; P =0.038), mostly because of a reduction in target lesion revascularization. The rate of spontaneous nonfatal myocardial infarction and stent thrombosis were extremely low, with no significant difference between the 2 groups (0.6% versus 0.8%; P =0.513 and 0.1% versus 0.4%; P =0.174, respectively). Conclusions: In ACS patients receiving percutaneous coronary intervention, DP-DES was noninferior to BP-DES with regard to patient-oriented composite outcomes at 12 months after index percutaneous coronary intervention. Registration: URL: https://wwwclinicaltrials.gov ; Unique identifier: NCT02193971.